Hubungan Peran Kelompok Tani Dengan Kapasitas Petani Penangkar Benih Padi Sawah (Oriza Sativa L) Di Kabupaten Lampung Timur - Robinson Putra; Amiruddin Saleh; Ninuk Purnaningsih (Institut Pertanian Bogor, 2016)
The aim of this research are to: (1) analyze the role of the seed farmers in East Lampung regency; (2) analyze the capacity ofseed farmers in East Lampung regency; (3) analyzing role of farmer groups’relation with the capacity of seed farmers for paddy rice sources in East Lampung regency. The study was conducted in East Lampung district seed farmers group with total sample of 59 farmers seed breeders. The method of analysis was used Pearson's correlation matrix. The results showed that: (1) the role of the seed farmers group as partnership forum and marketing units is the most important with the higher category results than group's role as learning forum and production units with the medium category; (2) the capacity of farmers in the seed production preparation and sustainability efforts was in the high category, while in the mastery of innovation, the application of technology components, and marketing orientation was in the medium category; (3) generally there is a significant corelation between the role of farmer groups with the capacity of breeder farmers with the exception relation of partnership forum, unit production and marketing unit with the application of technology components, and marketing unit with the marketing orientation and a partnership.Keywords: capacity, farmer breeders, role of group, seed